Haploid Mammalian Genetic Screen Identifies UBXD8 as a Key Determinant of HMGCR Degradation and Cholesterol Biosynthesis - Loregger, Anke; Raaben, Matthijs; Tan, Josephine; Scheij, Saskia; Moeton, Martina; van den Berg, Marlene; Gelberg-Etel, Hila; Stickel, Elmer; Roitelman, Joseph; Brummelkamp, Thijn; Zelcer, Noam (Arteriosclerosis, thrombosis, and vascular biology, 2017)
The cellular demand for cholesterol requires control of its biosynthesis by the mevalonate pathway. Regulation of HMGCR (3-hydroxy-3-methylglutaryl coenzyme A reductase), a rate-limiting enzyme in this pathway and the target of statins, is a key control point herein. Accordingly, HMGCR is subject to negative and positive regulation. In particular, the ability of oxysterols and intermediates of the mevalonate pathway to stimulate its proteasomal degradation is an exquisite example of metabolically controlled feedback regulation. To define the genetic determinants that govern this process, we conducted an unbiased haploid mammalian genetic screen. We generated human haploid cells with mNeon fused to endogenous HMGCR using CRISPR/Cas9 and used these cells to interrogate regulation of HMGCR abundance in live cells. This resulted in identification of known and new regulators of HMGCR, and among the latter, UBXD8 (ubiquitin regulatory X domain-containing protein 8), a gene that has not been previously implicated in this process. We demonstrate that UBXD8 is an essential determinant of metabolically stimulated degradation of HMGCR and of cholesterol biosynthesis in multiple cell types. Accordingly, UBXD8 ablation leads to aberrant cholesterol synthesis due to loss of feedback control. Mechanistically, we show that UBXD8 is necessary for sterol-stimulated dislocation of ubiquitylated HMGCR from the endoplasmic reticulum membrane en route to proteasomal degradation, a function dependent on its UBX domain. We establish UBXD8 as a previously unrecognized determinant that couples flux across the mevalonate pathway to control of cholesterol synthesis and demonstrate the feasibility of applying mammalian haploid genetics to study metabolic traits.